A case presentation of Voriconazole therapy in a brochopulmonary dysplasia - Elaheh Amini; Firoozeh Nili; Fatemeh Nayeri; Tahereh Esmaeilnia; Hosein Dalili; Mamak Shariat (Mashhad University of Medical Sciences, 2015)
Premature infants may be more vulnerable to fungal infections because of their immature immune system, poorly developed epithelial skin and mucosal barriers, and the high rate of invasive procedures, such as central venous catheters and intubation, which compromise host defenses (eg, skin integrity).Voriconazole is a newer systemic antifungal agent effective against Candida and Aspergillus. There are few reports of its safe use in newborns. We report the first case report - a 29 gestational age-900 gram baby girl of safe Voriconazole use in a critically ill with profound pancytopenia -huge hepatosplenomegaly due to fungal infection resistant to amphotericin B.With beginning oral Voriconazole all liver functions tests what were severely abnormal returned normal with normalizing of the size of liver and spleen. It was noted to be safe and well tolerated by the newborn. Because of oral administration of it, voriconazole is a very good choice for fungal infections in neonates.